Model Pemberdayaan Masyarakat Islam Melalui Tradisi Kirab Jenang “Tebokan” Di Desa Kaliputu Kecamatan Kota Kabupaten Kudus - Nur Amalia, Intan (Community Development: Jurnal Pengembangan Masyarakat Islam, 2020)
The aimed thus research was described to Islamic’s community development by kirab jenang “tebokan” tradition’s in Kaliputu village, Kudus. Thus research used descriptive qualitative research method. Semi structure interview, observation and documentation had data collected. Main data research was taken kaliputu village communities had been participated in thus activities. Then It was given main result; 1) kaliputu village could been community development as Jenang Pioneer village’s; 2) Islamic’s community development model’s was part local community developmental.